2005
DOI: 10.1021/jp058078v
|View full text |Cite
|
Sign up to set email alerts
|

Potential Energy Surfaces of SimOn Cluster Formation and Isomerization

Abstract: The reaction paths for formation and isomerization of a set of silica SimOn (m = 2,3, n = 1−5) nanoclusters have been investigated using second-order pertubation theory (MP2) with the 6-31G(d) basis set. The MP2/ 6-31G(d) calculations have predicted singlet ground states for all clusters excluding Si3O2. The total energies of the most important points on the potential energy surfaces (PES) have been determined using the completely renormalized (CR) singles and doubles coupled cluster method including perturbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
50
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 50 publications
13
50
1
Order By: Relevance
“…This assumption is supported by accurate theoretical calculations which show the absence of a barrier for the SiO + SiO → (SiO) 2 and SiO + (SiO) 2 → (SiO) 3 reactions. Although a study by Pimental et al 26 reported a modest barrier for the latter (trimerisation) reaction, we could not verify this result and agree with the conclusion of Avramov et al 21 that a barrier for trimerisation does not exist. This conclusion is strongly supported by helium droplet experiments showing that this, and similar oligomerization reactions, proceed at temperatures as low as 0.37 K. 25 As many of our (SiO) N ground state clusters can simply be regarded as resulting from SiO insertions into a ring in the corresponding (SiO) N+1 isomer (and thus analogous to the trimerisation reaction) we expect at least these steps to involve very low or zero effective barriers.…”
contrasting
confidence: 99%
“…This assumption is supported by accurate theoretical calculations which show the absence of a barrier for the SiO + SiO → (SiO) 2 and SiO + (SiO) 2 → (SiO) 3 reactions. Although a study by Pimental et al 26 reported a modest barrier for the latter (trimerisation) reaction, we could not verify this result and agree with the conclusion of Avramov et al 21 that a barrier for trimerisation does not exist. This conclusion is strongly supported by helium droplet experiments showing that this, and similar oligomerization reactions, proceed at temperatures as low as 0.37 K. 25 As many of our (SiO) N ground state clusters can simply be regarded as resulting from SiO insertions into a ring in the corresponding (SiO) N+1 isomer (and thus analogous to the trimerisation reaction) we expect at least these steps to involve very low or zero effective barriers.…”
contrasting
confidence: 99%
“…The optimized geometry of other less symmetrical isomers lying at higher energies is also depicted in the same figures. Structures and energies are in good agreement with those reported in theoretical [1][2][3][4][5]11,[16][17][18] and experimental [19] work. The bond distances and angles of the structures shown in Figure 2 are given in Figure S1, Supporting Information.…”
Section: Original Articlessupporting
confidence: 87%
“…[1,3,[8][9][10] Møller-Plesset second-order perturbation theory (MP2) has been used to perform intrinsic reaction coordinate (ICR) and energy barrier calculations of several Si n O m clusters reactions, obtaining results in reasonable agreement with coupled cluster methods. [11] For the PES calculations performed in this work, scans at the MP2/6-31G(d) level of theory (including all electrons) were carried out at specific locations of the PES, to obtain more accurate energy values of possible transition states and barriers. All the calculations were performed with the Gaussian 03 Package.…”
Section: Original Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the CR-CCSD(T) and CR-CC(2,3) approaches (particularly, CR-CC(2,3)) provide very good results for single bond breaking [10-13,29-31, 33,34,37,40-44,89,91,92], and reaction pathways involving biradicals and similar cases of electronic quasi-degeneracies [42,[46][47][48][49][50][51]59,93,94], eliminating the failures of the conventional CCSD(T) and CCSD(TQ) methods in those multireference situations. The CR-CCSD(TQ),a and CR-CCSD(TQ),b extensions of CR-CCSD(T) provide further improvements in the results for single bond breaking [11][12][13]29,31,33], while helping to obtain reasonable accuracies in cases of multiple bond stretching or breaking [11][12][13]20,[28][29][30]36,[39][40][41]44,76] (cf., also, Ref.…”
Section: Introductionmentioning
confidence: 99%